2017
DOI: 10.3892/mco.2017.1523
|View full text |Cite
|
Sign up to set email alerts
|

Osseous choristoma of the tongue: A case report with dermoscopic study

Abstract: Osseous choristomas are rare benign lesions characterized by ectopic bone formation in the soft tissue of the head and neck region. Dermoscopy visualizes the morphological characteristics that are not observable by the naked eye, and may be used for the evaluation of calcification under the skin. The present study reports a case of an osseous choristoma arising in the tongue, and reveals the dermoscopic features of osseous choristoma from a surgical specimen. A 7-year-old boy was referred to the Department of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
6
0
4
Order By: Relevance
“…Most pediatric patients with lingual osseous choristoma are females (4 males, 13 females). Although these findings are consistent with previous reports [ 4 , 54 ], we could not identify the reason for the sexual predisposition. The patients' ages ranged from 5 years to 11 years (mean 9.3 years, median 10 years using Excel function).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Most pediatric patients with lingual osseous choristoma are females (4 males, 13 females). Although these findings are consistent with previous reports [ 4 , 54 ], we could not identify the reason for the sexual predisposition. The patients' ages ranged from 5 years to 11 years (mean 9.3 years, median 10 years using Excel function).…”
Section: Discussionsupporting
confidence: 65%
“…The patients' ages ranged from 5 years to 11 years (mean 9.3 years, median 10 years using Excel function). It has been demonstrated that most of the lesions develop as symptomless 3–50 mm masses located in the tongue's posterior third in the area of circumvallate papillae or close to the foramen caecum [ 4 , 54 ]. The findings reported in our manuscript are in line with previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histopathologically, lingual osseous choristoma is submucosally located and consist of well-developed lamellar bone and Haversian system. Osteoblastic and osteoclastic activity, cytological atypia or mitosis are not observed in the bone tissue [10].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 81%
“…Less than 100 cases of osseous choristomas of the oral and maxillofacial region have been reported in the English language literature, and the most common site is the tongue, especially the dorsal posterior third of the tongue near the foramen caecum and circumvallate papillae [5]. Gorini et al provided a comprehensive review of 67 cases of the lingual osseous choristomas [6], and eight additional cases of osseous choristoma of the tongue were reported since their review [5,[7][8][9][10][11][12]. Including newly reported cases and our case, the patients' age ranged from five to eighty-nine years (mean: 28.9), with majority of the patients being in the second or third decades of life, and a strong female predilection (male : female, 19 : 50) was observed.…”
Section: Discussionmentioning
confidence: 99%